Diurnal foraging ant–tree co‐occurrence networks are similar between canopy and understorey in a Neotropical rain forest. (5th March 2020) - Antoniazzi, Reuber; García‐Franco, Jose; Janda, Milan; Leponce, Maurice; Dáttilo, Wesley
Abstract: Discussion of the vertical stratification of organisms in tropical forests has traditionally focused on species distribution. Most studies have shown that, due to differences in abiotic conditions and resource distribution, species can be distributed along the vertical gradient according to their ecophysiological needs. However, the network structure between distinct vertical strata remains little‐explored. To fill this gap in knowledge, we used baits to sample ants in the canopy and understorey trees of a Mexican tropical rain forest to record the ant–tree co‐occurrences. We examined the ant–tree co‐occurrences in the canopy and understorey using complementary network metrics (i.e., specialization, interaction diversity, modularity, and nestedness). In addition, we evaluated co‐occurrence patterns between ant species on trees, using C‐score analysis. In general, we found no differences in the network structure, although the interaction diversity was greater in the understorey than in the canopy networks. We also observed that co‐occurrence networks of each vertical stratum featured four ant species in the central core of highly co‐occurring species, with three species unique to each stratum. Moreover, we found a similar trend toward ant species segregation in the both strata. These findings reveal a similar pattern of ant–ant co‐occurrences in both vertical strata, probably due to the presence of arboreal‐nesting ants in the understorey. Overall, we showed that despite the marked differences in species composition and environmental conditions between understorey and canopy strata, ant–tree co‐occurrences in these habitats could be governed by similar mechanisms, related to dominance and resource monopolization by ants. Abstract in Spanish is available with online material. Resumen: Tradicionalmente, la discusión de la estratificación vertical de los organismos en los bosques tropicales se ha enfocado en la distribución de especies. La mayoría de estudios han mostrado que, debido a las diferencias en las condiciones abióticas y la distribución de los recursos, las especies se distribuyen a lo largo del gradiente vertical de acuerdo a sus necesidades fisiológicas. Sin embargo, la estructura de las redes entre los distintos estratos verticales aún es poco explorada. Para llenar este vacío de conocimiento usamos cebos para muestrear hormigas en árboles de dosel y de sotobosque en un bosque tropical mexicano para registrar las coocurrencias árbol–hormiga. Nosotros examinamos las coocurrencias árbol–hormiga en el dosel y en el sotobosque usando métricas de redes complementarias (i.e., especialización, diversidad de interacciones, modularidad y anidamiento). Adicionalmente, evaluamos los patrones de coocurrencias entre especies de hormigas en los árboles usando el análisis C‐score. En general, no encontramos diferencias en la estructura de las redes entre dosel y sotobosque, aunque la diversidad de interacción fue mayor en las redes de sotobosque que en las redes de dosel. También observamos que en las redes de coocurrencias de cada estrato vertical se destacaron cuatro especies en el núcleo central de las especies de alta coocurrencia, con tres especies únicas para cada estrato. Además, encontramos una tendencia similar hacia la segregación de especies de hormigas en ambos estratos. Estos descubrimientos revelan un patrón similar de coocurrencias de hormiga–hormiga en ambos estratos verticales, probablemente por la presencia de hormigas en el sotobosque que anidan en el dosel. En general, nosotros mostramos que a pesar de las marcadas diferencias en la composición de especies y en las condiciones ambientales entre los estratos dosel y sotobosque, la coocurrencia de árbol–hormiga en estos hábitats podría estar gobernada por mecanismos similares, relacionados a la dominancia y monopolización de los recursos por las hormigas.